O desconforto térmico estival em Lisboa - uma abordagem bioclimática - Andrade, Henrique (1998)
THE SUMMER THERMAL STRESS IN LISBOA; A BIOCLIMATIC APPROACH. The summer frequency of hot days was studied, in Lisboa/Portela, with daily data from the period 1981/97. We used the Physiological Equivalent Temperature, an index of thermal confort based on the human energy balance, and calculated with air temperature, vapour pressure, wind speed and mean radiant temperature. It was assumed that mean radiant temperature was equal to air temperature, which is acceptable in the shade. The days were classifiend in two groups: hot days and very hot days, according to the thresholds of PET of 29ºC and 35ºC; 10% of the days had warm stress, with a maximum of frequency in July and a great interanual variability. The relation between the thermal discomfort and the wind regime was analysed. Most of the unconfortable days had breeze conditions, with the wind blowing from the East (from the estuary) during the morning; in the afternoon, the barometric gradient between the Ocean and the Iberian Peninsula increases, the breeze is replaced by a week northerly wind. The frequent occurence of strong northerly winds in summer is an important factor of reduction of the warm stress in Lisbon